2010
DOI: 10.1074/jbc.m109.091413
|View full text |Cite
|
Sign up to set email alerts
|

Gadd45b Mediates Fas-induced Apoptosis by Enhancing the Interaction between p38 and Retinoblastoma Tumor Suppressor

Abstract: Gadd45b has been known as a positive mediator of apoptosis induced by certain cytokines and oncogenes. Here, we identified Gadd45b as an effector of Fas-induced apoptosis and found that p38-mediated Rb hyperphosphorylation is one of the mechanisms of Fas-induced apoptosis in murine hepatocyte AML12 cells. Gadd45b has been shown to activate p38 through its physical interaction with MTK1 and induce apoptosis. However, in this study, we have showed that the function of Gadd45b during Fas-induced apoptosis in AML1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
39
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 29 publications
(27 reference statements)
3
39
1
Order By: Relevance
“…specific (Salvador et al 2013). It has been suggested that GADD45B may enhance or mitigate FAS-mediated apoptosis, depending on the cell type (Zazzeroni et al 2003, Cho et al 2010, thus the increase in GADD45B mRNA levels occurring with increased FASLG mRNA abundance may be part of either the apoptotic mechanism or a DNA repair mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…specific (Salvador et al 2013). It has been suggested that GADD45B may enhance or mitigate FAS-mediated apoptosis, depending on the cell type (Zazzeroni et al 2003, Cho et al 2010, thus the increase in GADD45B mRNA levels occurring with increased FASLG mRNA abundance may be part of either the apoptotic mechanism or a DNA repair mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…However, GADD45B has a number of additional activities that could be necessary for the viral lytic cycle. These include promoting DNA demethylation and Retinoblastoma (Rb) inactivation, processes that are important for a number of DNA viruses, including KSHV [74][75][76][77][78][79]. If our hypothesis that there are numerous SREs throughout the transcriptome is correct, it is likely that individual viruses require only a subset of these host genes for replication.…”
Section: Discussionmentioning
confidence: 99%
“…Both Gadd45b and Gadd45g interact with p21, and Gadd45b positively regulates its expression in senescing chondrocytes (Ijiri et al 2005 ), although the result of this interaction is unclear in other tissues and contexts (Gao et al 2009 ). Gadd45b facilitates p38-mediated activation of retinoblastoma tumor suppressor protein (Rb) by enhancing their interaction after Fas stimulation in murine hepatocytes (Cho et al 2010 ). It also mediates TGF-induced apoptosis in murine hepatic cells in a p38-and Smad-dependent manner and both Gadd45b and Gadd45g overexpression-induced apoptosis in HeLa cells.…”
Section: Roles For Gadd45b and Gadd45gmentioning
confidence: 98%